The snail and the whale - Donaldson, Julia, 1948- (Macmillan Children's Books, 2004)
A snail longs to see the world and hitches a lift on a whale's tail. Together they go on an amazing journey, past icebergs and volcanoes, sharks and penguins, and the snail feels very small in the vastness of the world. But when the whale is beached in a bay, it's the tiny snail who saves the day.